Vegetative propagation of native fruit species of páramo Thibaudia floribunda and Cavendishia bracteata by cuttings - Lina María López C.; Mariam Vásquez M.; Héctor Lancheros R.; Stanislav Magnitskiy (Agronomía Colombiana, 2017)
Cavendishia bracteata and Thibaudia floribunda (Ericaceae) are wild fruit shrubs native to the Andes region. This study aimed to characterize the rooting potential of basal and apical cuttings using naphthalene acetic acid (NAA) in different concentrations (0, 200, 500, or 1,000 mg L-1). In C. bracteata, the cutting position on the branch affected its sprouting and rooting, with apical cuttings presenting the best performance with auxin application. The rooting of cuttings was more successful in C. bracteata than in T. floribunda. NAA applications between 200 to 500 mg L-1 were more suitable for the propagation of C. bracteata due to the higher percentages of rooting and shoot production. For propagation of T. floribunda, the use of apical cuttings without the application of auxins is recommended. Adventitious roots in cuttings of both species were originated from parenchyma cells of the stem.